Photoshop elements 10 - Sheppard, Rob (Top 100 simplified tips & tricks., 2012)
Provides instructions for one hundred and five tasks for Adobe Photoshop Elements 10, covering such topics as adjusting images, working with RAW photographs, choosing local control features, creating adjustment layers, sizing and sharpening photographs, and using plug-ins.